(untitled) (Italian Journal of Public Health, 2008)
Background: Setting up Geographical Information Systems (GIS) on the existing health infrastructure and ongoing and planned interventions in public health in Tanzania is still in its infancy. While there are several activities on gathering information and attempts of documentation there does not exist an overall systematic approach of generally capturing all health related facts and bringing them together into a unique information system yet. In order to strengthen the information system in the health sector in general, and to assist Ministry of Health and Social Welfare (MoHSW) in better receiving an overview of health related infrastructure and intervention data for management purpose, a first-pilot GIS was built up in the Mbeya Region in cooperation with Tanzanian German Programme to Support Health (TGPSH)/Gesellschaft für technische Zusammenarbeit (GTZ). Methods: The Health-GIS contains information on all health facilities (HF) in the region and their infrastructure. Therefore, personal interviews were conducted in selected HF based on a comprehensive questionnaire. The spatial coordinates of the HF were taken with a Global Positioning System (GPS). In a relational database, the newly coded HF are linked to the gathered information pertaining to them and in a second step are analysed and visualised with help of GIS. Results: First results show newly collected geometry and attribute data for a considerable number of HFs in Mbeya Region, which are then supplemented by information on the street network lately surveyed during the fieldtrip. With the help of a database management system (DBMS) all information are stored and maintained within one health database. By their spatial relation, data may be analysed and mapped with a Health-GIS. Because of the targeted cooperation with people and institutions from the local health sector, the way for integrating the Health-GIS into the health planning infrastructure is open. Also, the funding of an IT group comprised of members from national and international institutions is another step to gaining local acceptance for the system. Conclusions: First steps have been taken to introduce the Health-GIS as a pilot project in the Mbeya Region. It has proved to be useful in order to collect the essential attributes of the HFs. Further development of the GIS will have to be taken into account simplicity of use. Hence this requires that the GIS needs to be integrated into the planning process.